Involving Local Wisdom in Kampai Island to Create Digital Storytelling - Donny Adiatmana Ginting; Muhammad Hassan (Budapest International Research and Critics University, 2021)
The research is aimed to create the learning media by using local wisdom in Kampai Island. Kampai Island has unique local wisdom called Datuk Panjang, an islamic preacher in the Kampai Island. The technology is applied in the learning media and converted to the digital form called digital storytelling. This research is research and development (R&D). Developing the learning media used 4-D design consists of define, design, development dan dissemination proposed by Thiagarajan. The learning media should fulfil valid and effective. Invalidating the learning media followed two stages and the learning media was validated by the expert in media technology, language and literature. Based on the validation, the digital storytelling has valid with the average 89% percent. Based on N-Gain, the digital storytelling was influential, with 76% of student passed the test and the gain score is 1 in the high level.